Enhancing Strategic Planning Through Marketing Performance Monitoring Applications - Mokoagow, Sitty Sherihulla; Noor, Laili Savitri; Paputungan, Saldin (SEAN Institute, 2024)
The role of marketing performance monitoring applications in improving strategic planning. The research method used was a literature review to identify the benefits and challenges of this application. The findings show that the app provides real-time data essential for performance analysis, enables in-depth understanding of market trends and consumer behaviour, and supports predictive analysis. However, challenges such as data overload, metrics alignment, and user adoption need to be addressed. These applications can enhance strategic planning if implemented appropriately and supported by effective data management systems, training, and relevant strategies. This conclusion provides insights into how marketing performance monitoring applications can positively influence strategic planning and assist organisations in achieving their business goals.